The effectiveness of creativity development program on problem solving skills and creativity in 4 to 6 year old children - Pishyar , Asal; Gholamali Lavasani , Masoud; Abedi, Ahmad; Afroz , Gholamali (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study was conducted with the aim of investigating the effectiveness of creativity development program on problem solving skills and creativity in preschool children. Method: This research was practical and semi-experimental with a pre-test-post-test design and a control group. The statistical population of the research included all children aged 4 to 6 in Isfahan city in 2021. In order to carry out the research, 30 children were selected by multi-stage cluster sampling method and were equally replaced in two experimental and control groups (15 people in each group). The members of the experimental group participated in the creativity development program during 12 sessions of 60 minutes, while the subjects of the control group did not receive any intervention. Subjects were evaluated using Torrance test of creative thinking (1974) and the London Shalis Tower Test (1982). The data were analyzed using covariance analysis. Results: The findings indicated that the creativity development program had a positive and significant effect on problem solving skills and creativity in preschool children (P<0.05). Conclusion: Therefore, from the findings of this research, it can be concluded that creativity development program can play an important role in improving problem solving skills and creativity in preschool children